2013
DOI: 10.1586/14737167.2013.841545
|View full text |Cite
|
Sign up to set email alerts
|

A systematic literature review of cardiovascular event utilities

Abstract: Cardiovascular disease (CVD) results in half of the non-communicable disease-related deaths worldwide. Rising treatment costs have increased the need for cost-utility models designed to compare the value of new and existing therapies. Cost-utility models require utilities, values representing the strength of preferences for various health states. This systematic literature review aimed to identify and evaluate utilities reported for stroke, myocardial infarction (MI) and angina. In total, 83 unique studies wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 116 publications
2
10
0
Order By: Relevance
“…The lower utility score of 0.33 for the year including a stroke (health state A) is similar to relatively low values reported by two previous studies assessing utility with the EQ-5D at time points during the first year after a stroke, ranging from 0.21 to 0.41 [ 30 , 32 ]. In addition, the lower utility for acute stroke than for chronic stroke (difference = 0.20) is consistent with the findings of a recent review, which noted that EQ-5D scores tend to improve over time following a stroke [ 27 ]. However, some contrasting results have also been reported, including those from two studies with relatively high utility values during the first year after a stroke [ 31 , 34 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The lower utility score of 0.33 for the year including a stroke (health state A) is similar to relatively low values reported by two previous studies assessing utility with the EQ-5D at time points during the first year after a stroke, ranging from 0.21 to 0.41 [ 30 , 32 ]. In addition, the lower utility for acute stroke than for chronic stroke (difference = 0.20) is consistent with the findings of a recent review, which noted that EQ-5D scores tend to improve over time following a stroke [ 27 ]. However, some contrasting results have also been reported, including those from two studies with relatively high utility values during the first year after a stroke [ 31 , 34 ].…”
Section: Discussionsupporting
confidence: 87%
“…A CUA requires health state utility values, which represent the strength of preferences for various health states and are used to calculate quality-adjusted life years (QALYs) [ 24 - 26 ]. A recent systematic review found that a wide range of published utility values are available to represent health states with cardiovascular conditions such as stroke, acute coronary syndrome (ACS), and heart failure [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The current study adds to this research by demonstrating that awareness of elevated risk of these medical conditions, rather than the conditions themselves, may also have a measurable impact on utility. As expected, the disutility of risk (health states 2 to 4) was smaller than the disutility of the medical conditions represented by health states 5 to 8 and quantified in previous research [5561]. However, the relatively small disutilities associated with ART risks, ranging from 0.018 to 0.049 (Table 5), could still have an impact on the outcomes of a cost-utility model comparing treatments that differ in terms of these risks.…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies have consistently demonstrated that health state utilities are significantly reduced as a result of bone problems [55, 56], renal disease [5759], and cardiovascular disease [60, 61]. The current study adds to this research by demonstrating that awareness of elevated risk of these medical conditions, rather than the conditions themselves, may also have a measurable impact on utility.…”
Section: Discussionmentioning
confidence: 52%
“…Previous cost-utility analyses of treatments for CKD and SHPT have used utilities for cardiovascular events and fractures from outside of the context of CKD due to the lack of utility data available for these events in this population [ 30 33 ]. However, the literature for cardiovascular events is highly variable [ 58 ], making it difficult to select the appropriate values for use in a model focusing on treatment of CKD. In addition, the majority of utilities for fractures have come from utility estimates in osteoporosis, which may not be relevant to patients with CKD [ 30 33 ].…”
Section: Discussionmentioning
confidence: 99%